Faktor Kemenangan Koalisi Suharsono-Halim dalam Pemenangan Pemilu Kepala Daerah Kabupaten Bantul Tahun 2015 - Putri, Masdiyan; Qodir, Zuly (Journal of Governance and Public Policy, 2017)
Regional head election (Election), which aims at selecting the regent and deputy regent is one part of the mechanism ofdemocracy, became the main gate in building leadership in the area. Bantul regency simultaneously implement the firstelection on December 9, 2015, followed by two pairs of candidates, namely Suharsono-Abdul Halim Musleh (Suharsono-Halim) promoted by a coalition of PKB, Gerindra, and supported by the PKS and the Democratic Party. Another coupleis Sri Suryawidati-Misbakhul Munir (Ida-Munir) promoted by a coalition of the PDI-P, Nasdem and supported by Golkarand PPP. Based on the results of counting of votes at the General Election 2015 Bantul regency, the victory won by thecouple Suharsono-Halim with a tally of 261 412 valid votes, or 52.80%. The problem underlying this study is that thedefeat of the incumbent against the new candidate, their political issues couples dolls, as well as their political dynastythat occurred in the district of Bantul. This study aims to identify factors that influence Suharsono-Halim victory in theelection district of Bantul in 2015. This study used a qualitative descriptive method, where data collection techniquesusing interviews, and documentation. Sampling using purposive sampling, where the speakers who will be interviewedare selected based considerations and an informant competent to answer questions researchers. The results of thisstudy the expression of that factor Suharsono win-Halim coalition partner in the election in Bantul district in 2015 wasinfluenced by three factors. The first coalition of political parties, which the coalition used is minimal coalition victory.Both political participation, community involvement Bantul in granting voting rights in the election in 2015 increasedcompared to the election in 2010 and the highest among the Gunung Kidul and Sleman districts, which also carry outthe election. The third modality, this modality consists of political capital, social capital, cultural capital and economiccapital. Political capital owned by Suharsono-Halim ie a split in the opposite camp, the strength of the network owned,as well as the utilization of the existing political issues, while the socially owned capital as a base period, figures figures,the trust of the community. For cultural capital owned by the couple in the form of titles and social strata owned, as wellas for economic capital have is that in political funds gained from internal party coalition, volunteers, as well as from thecandidate regent and deputy regent. This proves that the factor-Halim Suharsono coalition victory in the 2015 electionBantul district is the result of cooperation of various parties, namely the performance of the coalition of political parties,as well as community involvement in high political participation and modalities owned.